2016
DOI: 10.1142/s0217984916503413
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electron and hole transport layer with the electrode work function on perovskite solar cells

Abstract: The effects of electron and hole transport layer with the electrode work function on perovskite solar cells with the interface defects were simulated by using analysis of microelectronic and photonic structures-one-dimensional (AMPS-1D) software. The simulation results suggest that TiO2 electron transport layer provides best device performance with conversion efficiency of 25.9% compared with ZnO and CdS. The threshold value of back electrode work function for Spiro-OMeTAD, NiO, CuI and Cu2O hole transport lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Therefore, as a mandatory part, electrical simulations were performed thoroughly of investigated solar cells by the finite element method (FEM), which allows determining the current-voltage (J-V) characteristic curve of the solar cell. A set of necessary electronic parameters of materials was used for the calculation, which were adapted from the literature and summarized in Table S5 [35][36][37][38][39][40]. A more detailed description of the electrical simulation is provided in Section S3 and literatures [11,37].…”
Section: Coupled Opto-electrical Simulation Methodsmentioning
confidence: 99%
“…Therefore, as a mandatory part, electrical simulations were performed thoroughly of investigated solar cells by the finite element method (FEM), which allows determining the current-voltage (J-V) characteristic curve of the solar cell. A set of necessary electronic parameters of materials was used for the calculation, which were adapted from the literature and summarized in Table S5 [35][36][37][38][39][40]. A more detailed description of the electrical simulation is provided in Section S3 and literatures [11,37].…”
Section: Coupled Opto-electrical Simulation Methodsmentioning
confidence: 99%
“…The large amount of data available on perovskite absorber materials suggests that an increase in the performance of the electron transfer material (ETM) may lead to higher PCE and improved stability and can also reduce the hysteretic behavior in PSCs which describes the mismatch of the J – V curves depending on the voltage sweep direction decreasing the averaged power output . Several materials have been tested as ETMs, including TiO 2 , SnO 2 , ZnO, and WO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Dzikri et al [ 71 ] and Kim et al [ 72 ] reported the work functions of 5.53 and 5.4 eV, respectively. The predicted work function of CuSCN also compares with those of other commonly used hole transport layer materials: Spiro-OMeTAD = 4.9, PEDOT:PSS = 5.1 eV, NiO x = 5.4 eV, V 2 O 5 = 5.4 eV, MoO x = 5.3 eV, WO 3 = 5.35 eV, and GO = 4.9 eV [ 73 , 74 ]. The close match between the work function of CuSCN and the highest occupied molecular orbital level of most perovskite materials (e.g., CH 3 NH 3 PbI 3 = –5.4 eV) ensures good alignment of energy levels, which will give rise to improvements in device efficiency.…”
Section: Resultsmentioning
confidence: 95%